NAVIGATING THE SPECTRUM OF HUMANITY IN AS BRIGHT AS HEAVEN (2018) BY SUSAN MEISSNER - Ilham Ali, Muhammad; Ismail, Ismail; Pabur, Herminus Efrando (Universitas Pakuan, 2024)
This research aims to analyze the social situations and interpret quotes that express the social conditions and human value as reflected in the novel